The Influence of Motivation, Emotional Intelligence, Personality and Leadership on Employee Performance Through Job Satisfaction as a Mediating Variable - Kelvin,; Muchsinati, Evi Silvana (Jurnal Manajemen, 2023)
The purpose of this study was to determine the effect of motivation, emotional intelligence, personality, and leadership on employee performance through job satisfaction. The methodology for the research is quantitative. This study falls under the category of causal comparative research, and its sample or population totals 227 workers from rural credit banks in Batam City. The partial least squares (PLS) method of data analysis is employed. PLS gives this approach the fundamental capacity to examine the causal link between the independent and dependent variables and to validate and reliably test the results. The results showed that employee performance can be significantly influenced by motivation, emotional intelligence, personality, and leadership. It was also found that job satisfaction can significantly mediate the relationship between motivation and employee performance, emotional intelligence and employee performance, personality and employee performance, and leadership and employee performance